Presentation of knowledge in the production of entomophages - Chernova, I. (Energy and Automation, 2025)
The article is devoted to the issue of knowledge representation in the production of entomophages based on the use of ontologies. The aim of the study is to develop an ontological knowledge base in entomophages production. The object of the research is knowledge about the processes of managing the production of entomophages. The subject of the research is the digitalization of entomophages production management processes. Research methods – structural synthesis, ontological analysis, synergistic approach, software environment Visual Understanding Environment. The relevance of the indicated research direction is substantiated; well-known works on the application of ontologies are noted, in particular, in the processes of: decision-making support, intelligent control of technological complexes; ontological modeling of a knowledge base for travel organization, creation of an ontological glossary; development of a dictionary and ontology for modeling insect natural history data, etc. An ontological knowledge base in the production of the entomophages Habrobracon hebetor has been developed. The structure of the knowledge base contains: classes "Human actions in production management processes", "Quality control of entomological products", "Technological processes", "Formalization of knowledge regarding production processes", "Precedentes", "Decision support", "Ensuring the quality of entomological products"; concepts and built-in ontologies "Processes of the production of entomophage Habrobracon hebetor", "Thesaurus of intellectual support for decision-making in the production of entomophages". The results of the study make it possible to increase the efficiency of the management processes of complex biotechnical production due to the digitalization of knowledge, the growth of the level of competence of biotechnologists. Key words: knowledge base, entomophages production, ontologies, decision support